TRAFFIC SIMULATION TRAFFIC SYSTEM USING SIMEVENTS MATLAB - ERWIN (INFOKOM (Informatika & Komputer), 2018)
Road traffic is a supporting medium that is essential to various means of landtransportation that connect various locations and even large cities. Smooth traffic is agood parameter of the management of a city, also as a sign to determine thetechnological and economic development in the city. As the rate of civilization grows, aswell as the number of people, the road traffic becomes more crowded, so that, congestionoccurs to an alarming level. The solution to breaking down the congestion problem is byapplying some methods and traffic engineering. However, implementing some methodsand traffic engineering without proper planning, will lead to high costs and less optimalresults.In this article we proposed a traffic simulation system called as "LINTAS", as atool in trying to decipher the traffic jam. The exact method and traffic engineering, beforeit is tested in a real way, is first simulated through the LINTAS system, so that it can beknown its effectiveness. LINTAS are built using the SimEvents toolbox and run onMATLAB-Simulink software. The LINTAS simulator is performed based on themathematical sciences, especially the field of queueing theory.